KUALITAS PELAYANAN JASA KEAGENAN KAPAL DAN KOMUNIKASI INTERPERSONAL PADA PERUSAHAAN PELAYARAN - Anton Pangihutan; Muhammad Thamrin; Asep Suparman (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
The study aimed to analyze the relationship of services quality of ship agency, interpersonal communication with user satisfaction in PT Buana Listya Tama, both partially and simultaneously. The research uses quantitative methods by doing survey, and the data were analyzed using correlation and regression. The results show that the variables of interpersonal communication and service quality have a significant relationship either partially or simultaneously with customer satisfaction. Variable quality of service has a positive and significant correlation with t value of 4.905 and greater than t table of 1.998 so that Ho is rejected and Ha is accepted. Interpersonal communication variables also has a positive correlation with customer satisfaction with the value of tcount equals to 6,108 and greater than t table of 1.998 so that Ho is rejected and Ha is accepted. Through the F test it is found that the quality of service and interpersonal communication are simultaneously correlated with satisfaction where the F count is larger than F table (90.839> 2.75) so that Ho is rejected and Ha is accepted. The coefficient of determination (R Square) between variables is 0.749 or 74.9%. The amount of the contribution of service quality and interpersonal communication on customer satisfaction is 74.9%, whereas 25.1% influenced by other factors not examined.